Diagnostic value of HMGB-1 and Acetylcholinesterase in Assessing the Prognosis of Patients with Acute Pancreatitis: . - Guo, Pengfei; Chen, Wanfang; Zhang, Danping; li, yan (Journal of Medical Biochemistry, 2024)
Aim: Acute pancreatitis (AP) is a disorder of tissue digestion caused by abnormal activation of pancreatic enzymes, which may lead to multi-organ failure and ultimately death as the disease progresses. How to quickly and accurately evaluate the progression of AP has always been a hotspot and difficulty in clinical research. Methods: Sixty-four AP patients admitted to our hospital between August 2022 and June 2023 and 60 healthy people during the same period were selected for retrospective analysis, with AP patients as the observation group and healthy people as the control group. HMGB-1 and AChE levels were detected in both groups, and the diagnostic value of HMGB-1 and AChE for AP was analyzed using the receiver operating characteristic (ROC) curve. Subsequently, the differences in the expression of HMGB-1 and AChE in AP patients with different severities were further observed. In addition, we detected albumin (ALB), transferrin (TRF), and total protein (TP) in the observation group and analyzed their correlation with HMGB-1 and AChE. Finally, a 6-month prognostic follow-up was performed to analyze the predictive value of HMGB-1 and AChE for poor prognosis in AP using ROC curves. Results: Compared with the control group, HMGB-1 was higher in the observation group, which was positively correlated with the severity of AP (P<0.05); while AChE was lower, which was negatively correlated with the severity of AP (P<0.05). HMGB-1+AChE had a sensitivity of 48.44% and a specificity of 88.33% for the diagnosis of AP (P<0.05, cut-off>0.639). In addition, HMGB-1 and nutrient protein were positively correlated and AChE and nutrient protein were negatively correlated in the observation group (P<0.05). Through the prognostic follow-up, it was seen that the diagnostic sensitivity of HMGB-1+AChE for poor prognosis of AP was 95.65% and the specificity was 65.85% (P<0.05). Conclusion: HMGB-1 was elevated in AP,and AChE was decreased in AP, both of which have excellent diagnostic effects on the occurrence and poor prognosis of AP.